Impact of motion blur on stereo‐digital image correlation with the focus on a drone‐carried stereo rig. (25th October 2018) - Balcaen, R.; Lavatelli, A.; Jiménez‐Peña, C.; Pfeiffer, H.; Zappa, E.; Debruyne, D.
Abstract: Stereo‐digital image correlation (DIC) is a wide‐spread technique in the field of experimental mechanics for measuring shape, motion, and deformation and it is frequently used for material identification by using inverse methods (e.g., virtual fields method and finite element model updating). New applications emerge due to the reached maturity level of the technique, which poses new challenges towards reaching a desired level of accuracy in operating conditions. In this work, the possibility of a drone carrying an in‐house‐made portable DIC setup is explored, and the effect of the drone‐induced vibrations on the accuracy of stereo‐DIC for shape and strain measurement is evaluated. During acquisition, the relative motion between the camera system and the measured item generates motion‐blurred images. The effect of this phenomenon on the precision of stereo‐DIC is further evaluated in this paper.